The documentation of the old road projects in the province of Badajoz in the 19th century - Sanz Caballero, Isabel Mª; Vivas Moreno, Agustín (Revista General de Información y Documentación, 2021)
The present work aims to analyze the documentation of the road projects that were carried out in the province of Badajoz throughout the 19th century. A tour is made of the concept of public works, institutions that generated the documentation and the legislation under which they were conceived. Also, an analysis is made of the series that was preserve until 2010 in the Archive of the Territorial Service of Badajoz of the Ministry of Mobility, Transport and Housing of the Junta de Extremadura, being transferred that year to the Provincial Historical Archive of Badajoz, where it is preserved today. Through this documentary analysis, we will be able to verify the characteristics of the documentation before which we find ourselves, as well as its historical purpose. The methodological criteria followed have been those related to documentary techniques (documentary identification, classification and description) and those related to historical analysis. As a result, the road projects during the 19th century in the province of Badajoz are identified, their documentary structure is analyzed and the architects who participated in these road projects.